Penatalaksanaan Holistik Pada Pasien Wanita Usia 42 Tahun dengan Hipertensi dan Diabetus Melitus Tipe 2 dengan Neuropati Diabetikum Melalui Pendekatan Kedokteran Keluarga di Puskesmas Natar - Annisa Ridha Salsabilla; Azelia Nusadewiarti (CV. Jasa Sukses Abadi, 2023)
The current pattern of disease incidence has undergone changes which are characterized by epidemiological transitions. Changes in disease patterns that were originally dominated by infectious diseases turned to non-communicable diseases. Hypertension and Diabetes Mellitus are one of the non-communicable diseases which are very serious health problems both in the world and in Indonesia. The purpose of this case report is to implement a holistic and comprehensive family doctor service by identifying risk factors, clinical problems, and patient management based on evidence-based medicine with a patient-centered and family approach. This study is a case report study. Primary data were obtained through history taking (autoanamnesis from the patient and alloanamnesis from the patient's family), physical examination and home visits. Secondary data were obtained from the patient's medical record. Assessment is based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. Patient Mrs. E is 42 years old, has been diagnosed with hypertension and type 2 diabetes mellitus with neuropathy has concerns about his health condition getting worse. The patient's hope is that the complaints disappear completely and do not recur, so they can be comfortable with their activities as usual. The patient's limited knowledge of the illness and an unfavorable lifestyle are factors that cause problems that occur in patients and their families. The diagnosis of hypertension and type 2 diabetes mellitus with neuropathy in this case is in accordance with several theories and critical studies from recent research. Management has been given in accordance with the management guidelines. There is good progress in patients starting from decreased clinical symptoms to changes in behavior after an intervention based on evidence-based medicine that is family-approach and patient-centered.